Management Changes in MRO business through product lifecycle - Sivusuo, Jaakko; Takala, Josu (De Gruyter Open, 2016)
Nowadays organizations and entire industries have faced the challenges of globalization and rapid technological development. These changes have brought new kind of competition and it has shaped and mixed organizations traditional business logic. This research is based on multiple case studies where the focus is on management changes through product lifecycle management. Emphasis is on MRO (Maintenance, repair, overhaul) providers and how they implement dynamic capabilities through product life cycle management. MRO is abbreviation for Maintenance, repair and overhaul and it is a commonly used in Aerospace industry. The study identifies several products in various stages of the life-cycle and thus identify the essential changes related to management. The stages that study identifies are Learning phase, Productisation phase and PBL phase. These phases can be used for clarifying dynamic capabilities in MRO markets.
Keywords: dynamic capabilities; service business; MRO – business; business model; aerospace; fi=Tuotantotalous|en=Industrial Management|